2009
DOI: 10.1038/onc.2009.180
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 induces an epithelial–mesenchymal transition phenotype in human breast cancer cells

Abstract: Breast tumor interleukin-6 (IL-6) levels increase with tumor grade, and elevated serum IL-6 correlates with poor breast cancer patient survival. Epithelial–mesenchymal transition (EMT) phenotypes such as impaired E-cadherin expression or aberrant Vimentin induction are associated with enhanced metastasis and unfavorable clinical outcome in breast cancer. Despite this fact, few tumor microenvironment-derived extracellular signaling factors capable of provoking such a phenotypic transition have been identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
541
5
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 647 publications
(570 citation statements)
references
References 32 publications
21
541
5
3
Order By: Relevance
“…In this study, transient expression of IL-6 dramatically reduced E-cadherin protein by 24 h, and constitutive expression of IL-6 led to an EMT in which Snail, Twist, vimentin and N-cadherin were induced, along with the development of more invasive tumors in mice. Conversely, Twist overexpression in MCF-7 caused an EMT along with high IL-6 expression and STAT3 activation [25]. This finding illustrated that not only could IL-6 induce an EMT, but EMT itself could result in production of IL-6.…”
Section: Cancer-associated Fibroblasts As a Potential Source Of Il-6 mentioning
confidence: 85%
See 2 more Smart Citations
“…In this study, transient expression of IL-6 dramatically reduced E-cadherin protein by 24 h, and constitutive expression of IL-6 led to an EMT in which Snail, Twist, vimentin and N-cadherin were induced, along with the development of more invasive tumors in mice. Conversely, Twist overexpression in MCF-7 caused an EMT along with high IL-6 expression and STAT3 activation [25]. This finding illustrated that not only could IL-6 induce an EMT, but EMT itself could result in production of IL-6.…”
Section: Cancer-associated Fibroblasts As a Potential Source Of Il-6 mentioning
confidence: 85%
“…IL-6 induced significant migration of MDA-MB-231 human breast carcinoma cells, but not of MCF-7 or T-47D breast carcinoma cell lines [24], suggesting that it could potentiate the invasive phenotype. This work led to the key discovery by Sullivan and colleagues that IL-6 could induce EMT in ER alpha positive MCF-7 breast cancer cell lines cultured in three-dimensions (3D) [25]. In this study, transient expression of IL-6 dramatically reduced E-cadherin protein by 24 h, and constitutive expression of IL-6 led to an EMT in which Snail, Twist, vimentin and N-cadherin were induced, along with the development of more invasive tumors in mice.…”
Section: Cancer-associated Fibroblasts As a Potential Source Of Il-6 mentioning
confidence: 99%
See 1 more Smart Citation
“…These changes in cell morphology are associated with several human cancers and may result in metastasis. 11,13,14 Cancer cells must breach the basement membrane to invade the surrounding tissue. Studies have shown that cancer cells increase secretion of matrix metalloproteinases (MMPs), which are enzymes that degrade the basement membrane, thereby facilitating their ability to invade.…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB may influence Snail expression through the AKT pathway and directly stabilize Snail activity [73]. This is particularly important for integrating inflammation pathways, such as interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), which have been linked to EMT in pathological conditions [74]. Other pathways such as Notch have also been shown to act synergistically with TGF-β to express Slug in the developing embryo [75].…”
Section: Discussionmentioning
confidence: 99%